MANAJEMEN PRODUKSI KONTEN CAROUSEL PADA AKUN INSTAGRAM @ACMOBILPREMIUM99 OLEH PT LOPOKOPI DIGITAL SHANKARA - Bianka Dwinanda Larasati; David Rizar Nugroho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research examines the process of producing visual content on a client's Instagram account in a creative company engaged in marketing agency, PT Lopokopi Digital Shankara, which focuses on marketing activities through social media, websites, SEO, advertising and so on which include digital marketing. Through a qualitative approach, this research applies POAC theory, namely planning, organization, implementation/movement, and supervision. The data collection techniques used are observation, active participation, interviews, and literature studies collected during the implementation of the internship program for five months. The results showed that the supporting theories used were in line with those carried out by PT Lopokopi Digital Shankara in implementing carousel content production on the @acmobilpremium99 account, besides that teamwork has an important role in all stages of the carousel content production process.